Studies of the species barrier between Drosophila subobscura and D. madeirensis IV. A genetic dissection of the X chromosome for speciation genes - Khadem, M. (2021)
The genetics of four traits contributing to the isolation mechanism between the two closely related species of Drosophilu belonging to the obscuru group, D. subobscura and D. madeirensis, have been investigated, especially regarding the influence exerted by the X chromosome. This chromosome has been roughly dissected genetically by the use of four markers. It was found that factors affecting viability of backcross males are spread from the centromeric end of the chromo some up the region marked by Bx. Three sections were responsible for male sterility/fertility. The abnormal head shape of the backcross males was affected by factor(s) on the madeirensis and the subobscura sex chromosome located at the region of MAD1 inversion. Finally, an abnormal trait in these males (presence of extra sex combs) was found to be controlled by four sections, two on the madeirrnsis X chromosome and two on the subobscuru one.